High prevalence and a long delay in the diagnosis of primary aldosteronism among patients with young‐onset hypertension. (22nd February 2021) - Alam, Sarah; Kandasamy, Devasenathipathy; Goyal, Alpesh; Vishnubhatla, Sreenivas; Singh, Sandeep; Karthikeyan, Ganesan; Khadgawat, Rajesh
Abstract: Background: Despite being the most common cause of secondary hypertension, prevalence of primary aldosteronism (PA) among patients with young‐onset hypertension (YH ‐ age of hypertension onset <40 years) remains poorly studied. Objective: We assessed the prevalence of PA in patients with YH referred for evaluation of secondary hypertension. Design and Patients: In this prospective, cross‐sectional study, 202 patients with YH, visiting endocrine and cardiology clinics of All India Institute of Medical Sciences, India, were evaluated. Measurements: Primary aldosteronism was screened by measuring plasma aldosterone concentration (PAC) and direct renin concentration (DRC) and calculating aldosterone‐to‐renin ratio (ARR), followed by confirmatory saline infusion test (SIT) according to Endocrine Society Guideline. Those confirmed with post‐SIT PAC >5 ng/dl underwent adrenal computed tomography (CT), followed by adrenal venous sampling (AVS). Results: Of 202 YH patients, 38 (18.8%) screened positive, and PA was confirmed in 36 (17.8%). The mean age was 43.9 ± 10.9 years, and median duration of hypertension was 10.5 (3.5–18) years. The prevalence of PA increased with grade of hypertension (8.1% in grade 1 to 37.1% in grade 3), number of antihypertensive medications (2.5% in those taking ≤1 to 50% in those taking ≥4 medications) and severity of hypokalaemia (0% in potassium >5 to 85.7% in potassium <3.5 mmol/L). The prevalence of PA by age of hypertension onset was highest in age group 30–39 years (31.3%). Conclusions: There is a high prevalence and a long delay in diagnosis of PA among patients with YH, and YH should be considered as a separate high‐risk category in PA screening algorithm.